A volta a Portugal em bicicleta como fator promocional da cidade de Macedo de Cavaleiros - Joana Isabel Batista Ribeiro (2016)
In Portugal, there has been a significant decrease in population in the northeast of the country and the resident population in that areas is increasingly older. In addition, it is noted that the sports chapter in that regions shows lack of development.The Volta a Portugal em Bicicleta is now back to the northeast of Portugal. In 2016, the city of Macedo de Cavaleiros witnessed the finish of the third stage of the competition, 19 years after the last arrival.In order to change this situation, this paper aims to evidence the Volta a Portugal em Bicicleta as a development and promotional factor of Macedo de Cavaleiros city.We opted for the use of qualitative methods for the research. Interviews were conducted to six identities that represent several areas of activity in the city and we proceeded to the collection of reports about the day's stage at issue, in sports and generic daily newspapers and regional weekly newspapers.The outcomes of the investigation showed to be in accordance with the literature reviewed. By this work we can conclude that: the policies pursued by the local authority have the purpose of developing nature tourism; the sporting reality of the city of Macedo de Cavaleiros is far from the expected, once there is a need to invest in facilities and sports offer; for these regions, the organization of events always creates economic, social and tourism impacts, and leaves legacy into the community memory.In that direction, we can also conclude that the organization's stage of Volta a Portugal em Bicicleta can act as booster and promotional factors of the city of Macedo de Cavaleiros.